2015
DOI: 10.1097/hjh.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the prevalence of hypertension in Nigeria

Abstract: Our findings suggest the prevalence of hypertension is high in Nigeria, and the overall awareness of raised blood pressure among hypertension cases is low in the country. We hope this study will inform appropriate public health response towards reducing this burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
154
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(184 citation statements)
references
References 45 publications
16
154
14
Order By: Relevance
“…Although we found a high proportion of individuals with elevated blood pressure during the community screening events (NNS = 5), this was lower compared to previous studies in Lagos [13]. The prevalence of hypertension in Lagos is high [1,2] and we expected a high yield of participants for the pilot program through the community screening events.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Although we found a high proportion of individuals with elevated blood pressure during the community screening events (NNS = 5), this was lower compared to previous studies in Lagos [13]. The prevalence of hypertension in Lagos is high [1,2] and we expected a high yield of participants for the pilot program through the community screening events.…”
Section: Discussioncontrasting
confidence: 80%
“…In Lagos, Nigeria, around 33% of the population suffers from hypertension [1,2], which is higher than the country’s overall prevalence of 29% [3]. Hypertension is the main risk factor for cardiovascular disease (CVD) and associated morbidity and mortality [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Nigeria, it has been projected that the number of cases of hypertension might hit 39.1 million by 2030 going by the current trend. 21 The present study found a prevalence of hypertension of 12.6% in District Hospital Awgu in 2016. This finding is comparable with what had been previously reported for Nigeria and Eastern Nigeria by some researchers.…”
Section: Discussionsupporting
confidence: 50%
“…In Nigeria, the estimated hypertension prevalence (systolic blood pressure (BP) ≥ 140 mmHg or diastolic BP ≥ 90 mmHg) is 28.9% among people aged 15 years and older [3]. It is well established that long-term treatment, which includes behavioral adaptations (e.g., weight control, reduced salt intake, regular exercise, smoking cessation and moderate alcohol use) and pharmacotherapy if needed, reduces BP and, concomitantly, the risk of developing CVD and other hypertension-related complications [4].…”
Section: Introduction Backgroundmentioning
confidence: 99%